2014
DOI: 10.1371/journal.pone.0106795
|View full text |Cite
|
Sign up to set email alerts
|

The Expression Pattern of microRNAs in Granulosa Cells of Subordinate and Dominant Follicles during the Early Luteal Phase of the Bovine Estrous Cycle

Abstract: This study aimed to investigate the miRNA expression patterns in granulosa cells of subordinate (SF) and dominant follicle (DF) during the early luteal phase of the bovine estrous cycle. For this, miRNA enriched total RNA isolated from granulosa cells of SF and DF obtained from heifers slaughtered at day 3 and day 7 of the estrous cycle was used for miRNAs deep sequencing. The results revealed that including 17 candidate novel miRNAs, several known miRNAs (n = 291–318) were detected in SF and DF at days 3 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
65
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(69 citation statements)
references
References 73 publications
(74 reference statements)
2
65
1
1
Order By: Relevance
“…Five of the 9 miRNAs confirmed to be upregulated in atretic follicles in the present study (miR-21-5p, miR-21-3p, miR-222, miR-155, and miR-199a-5p) were also found to be increased in subordinate relative to dominant follicles on day 3 of the bovine estrous cycle using deep-sequencing rather than microarray [12]. Another miRNA, miR-378, was previously shown, together with miR-21-5p, to increase in expression in subordinate and anovulatory follicles in horses [13], [14].…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…Five of the 9 miRNAs confirmed to be upregulated in atretic follicles in the present study (miR-21-5p, miR-21-3p, miR-222, miR-155, and miR-199a-5p) were also found to be increased in subordinate relative to dominant follicles on day 3 of the bovine estrous cycle using deep-sequencing rather than microarray [12]. Another miRNA, miR-378, was previously shown, together with miR-21-5p, to increase in expression in subordinate and anovulatory follicles in horses [13], [14].…”
Section: Discussionsupporting
confidence: 56%
“…A limited number of studies in cattle [11], [12] and pigs [8] have reported genome-wide miRNA expression profiles associated with follicle atresia. Five of the 9 miRNAs confirmed to be upregulated in atretic follicles in the present study (miR-21-5p, miR-21-3p, miR-222, miR-155, and miR-199a-5p) were also found to be increased in subordinate relative to dominant follicles on day 3 of the bovine estrous cycle using deep-sequencing rather than microarray [12].…”
Section: Discussionmentioning
confidence: 99%
“…During the course of mammalian folliculogenesis, different miRNAs are expressed in theca cells, granulosa cells (Salilew-Wondim et al, 2014;Gebremedhn et al, 2015), cumulus-oocytecomplex (Abd El Naby et al, 2013), follicular-fluid (Sohel et al, 2013) and the corpus luteum (McBride et al, 2012;Maalouf et al, 2016b). We have previously shown significant differences in the expression of et al, 2015).…”
Section: Expression Dynamics Of Mirnas During Follicular Developmentmentioning
confidence: 99%
“…Interestingly, the extent of differences in the relative abundance of miRNAs in granulosa cells of the two follicular categories was minimal at day 3, whereas it was much pronounced at day 7 and 19. However, irrespective of the day of estrous cycle, miR-26a, miR-10b and the let-7 family members were the most abundantly expressed miRNAs in granulosa cells of both dominant and subordinate follicles (Salilew-Wondim et al, 2014;Gebremedhn et al, 2015) signifying their cellular housekeeping role in bovine follicular development. The dynamic nature of miRNA expression has been also evidenced in ovine species during follicular-luteal transition in which miR-21, miR-125b, let-7a and let-7b were the most abundantly expressed miRNAs during comparative analysis of ovine growing follicles, preovulatory follicles, early and late corpus luteum (McBride et al, 2012).…”
Section: Expression Dynamics Of Mirnas During Follicular Developmentmentioning
confidence: 99%
“…Several studies have used more defi ned populations of ovarian somatic cells or have compared the changes in miRNA expression in extracellular vesicles (i.e., exosomes and microvesicles) isolated from follicular fl uid collected at discrete periods of follicle development. Briefl y, comparisons of miRNA expression of granulosa cells of subordinate and dominant follicles during the early luteal phase of the bovine estrous cycle using RNAseq identifi ed signifi cant differential miRNA expression (Salilew-Wondim et al 2014 ). In granulosa cells isolated from mice following a superovulation protocol, a small number of miRNA in granulosa cells were found to change temporally with respect to administration of an ovulatory dose of the LH mimic, human chorionic gonadotropin (hCG) (Fiedler et al 2008 ).…”
Section: Ovarian Mirna Expression Profilingmentioning
confidence: 99%